Pencegahan Fraud dalam pengelolaan alokasi dana desa - Sarwenda Biduri; Hadiah Fitriyah; Putri Febriana (Politeknik Ganesha Medan, 2022)
This study has a purpose to analyze the Effect of Presentation of Village Financial Statements, Internal Controls, and Competence on Fraud Prevention in Village Fund Allocation Management (Study on Villages in Sidoarjo Regency). Each village is represented by 4 people, namely the Village Head, Village Treasurer, Village Secretary, and BPD in Tanggulangin District, Sidoarjo Regency, namely 19 villages including Kalidawir, Kedensari, Kalitengah, Kalisampurno, Kedung Banteng, Kedung Bendo, Banjar Asri Village, Banjar Panji, Boro, Gempol Sari, Long Algae, Ketapang, Ketegan, Kludan, Ngaban, Putat, Penatarsewu, Randegan, and Sentul. Researchers used quantitative research with an associative approach and used primary data sources. The sampling method used is the saturated sampling technique method because the population is relatively small. The sample in this study were 76 respondents. The data used is primary data. The data analysis method used in this study is Multiple Linear Regression with SPSS 25. The results of this study indicate that the Presentation of Village Financial Statements Affects Fraud Prevention in Village Fund Allocation Management. Internal Control Affects Fraud Prevention in the Management of Village Fund Allocation. Competence Influencing Fraud Prevention in Village Fund Allocation Management.